Should childhood immunisation be compulsory?. Issue 4 (1st August 1999) - Bradley, P
Abstract : Immunisation is offered to all age groups in the UK, but is mainly given to infants and school-age children. Such immunisation is not compulsory, in contrast to other countries, such as the United States. Levels of immunisation are generally very high in the UK, but the rates of immunisation vary with the public perception of the risk of side effects. This article discusses whether compulsory vaccination is acceptable by considering individual cases where parents have failed to give consent or have explicitly refused consent for their children to be immunised. In particular, the rights of: a parent to rear his/her child according to his/her own standards; the child to receive health care, and the community to be protected from vaccine-preventable infectious disease are considered. The conclusion of the article is that compulsory vaccination cannot, with very few exceptions, be justified in the UK, in view of the high levels of population immunity which currently exist.